Analysis of Mathematical Communication Ability in Set Materials - Nuraini Nuraini; Putri Yuanita; Atma Murni; Yenita Roza (Urogram Studi Pendidikan Matematika, Universitas IVET, 2023)
The background factor for this research is the importance of mathematical communication skills (KKM), but in practice there are still many students who have low abilities in mathematical communication. This study intends to provide an overview of students' mathematical communication skills (KKM) with indicators of drawing, mathematical expression and writing. The method used is descriptive qualitative in which the subject will use class VIII students of SMP N 13 Dumai totaling 30 people. The research instrument is in the form of three essay test questions. To obtain in-depth information, interviews were conducted with three students whose abilities were heterogeneous and selected from all students who took the test. The results of this study indicate that 26.67% of students are classified as high, 53.33% of students are classified as moderate and 20% of students are classified as low. The factor that causes the low ability of students' mathematical communication is the lack of students' ability to express mathematics